Cape Verde : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2005)
This paper focuses on Cape Verde's Growth and Poverty Reduction Strategy (GPRS). The GPRS is part of a broader strategic planning exercise that has been under way in Cape Verde and has as main pillars the Grand Options of the Plan 2002-05 (GOP) and the National Development Plan (NDP). The link between the NDP and the GPRS ensures global coherence of the planning instruments, thus facilitating management and monitoring of the various programs, and avoids duplication of efforts and procedures.